Recruitment Analysis Through Open Bidding Announcement in the Selection of Prospective Echelon II - Azhzhahiri, Bhasir (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
To get quality manpower, several phases of human resources management activity are needed. The initial phase of human resources management itself is started with recruiting to get eligible candidate. Currently the process of position fulfillment in government agency has been applying open position system, which is known as open bidding. Open position is a promise process that gives opportunity to employees outside the organization to hold position in the organization. The purpose of this system is to expand the scope of employee resources. Thus, the recruting process in open tender that determines the candidate’s success can be categorized into selection phase. If this phase runs well, good quality human resources will be attained as the result.